2001
DOI: 10.1177/1524838001002004001
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Focused Batterer Counseling for African American Men

Abstract: Research Summary:Clinicians and researchers have strongly recommended culturallyfocused counseling with African-American men arrested for domestic violence. An experimental clinical trial tested the effectiveness of this approach against conventional cognitive-behavioral counseling in all-African-American groups and in racially-mixed groups (N = 501). No significant difference was found in the reassault rate reported by the men's female partners over a 12-month follow-up period (23% overall). During that perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 44 publications
1
65
0
1
Order By: Relevance
“…Our findings also identify certain markers of likely drop outsnamely, men reporting lower levels of physical violence (i.e., perhaps reflecting greater denial of violence as common), who have lower incomes, are no longer involved in an intimate relationship with the woman they abused, and report higher levels of hostility are more likely to drop out of batterer treatment. These research findings are consistent with previous research both in terms of men's widespread denial and minimization of violence (e.g., Anderson and Umberson 2001;Hearn 1998;Heckert and Gondolf 2000), and in terms of preliminary suggestions that drop outs are not evenly distributed but are concentrated in groups exhibiting certain characteristics and life contexts (Daly and Pelowski 2000;Daly et al 2001;DeMaris 1989;Gondolf and Williams 2001;Saunders and Parker 1989). For instance, Cadsky et al (1996) found that clients who failed to self-identify problems with domestic abuse were more likely to drop out of treatment than those whose selfidentified problems matched the program focus.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings also identify certain markers of likely drop outsnamely, men reporting lower levels of physical violence (i.e., perhaps reflecting greater denial of violence as common), who have lower incomes, are no longer involved in an intimate relationship with the woman they abused, and report higher levels of hostility are more likely to drop out of batterer treatment. These research findings are consistent with previous research both in terms of men's widespread denial and minimization of violence (e.g., Anderson and Umberson 2001;Hearn 1998;Heckert and Gondolf 2000), and in terms of preliminary suggestions that drop outs are not evenly distributed but are concentrated in groups exhibiting certain characteristics and life contexts (Daly and Pelowski 2000;Daly et al 2001;DeMaris 1989;Gondolf and Williams 2001;Saunders and Parker 1989). For instance, Cadsky et al (1996) found that clients who failed to self-identify problems with domestic abuse were more likely to drop out of treatment than those whose selfidentified problems matched the program focus.…”
Section: Discussionsupporting
confidence: 89%
“…It is interesting that practitioners have begun to employ different frameworks to understand abusive men from diverse cultures, although still holding them responsible for their abusiveness (Tong 1998;Carrillo and Goubaud-Reyna 1998;Williams 1992Williams , 1998. Groups geared exclusively to African American men had greater relevancy when participants had a strong sense of cultural and racial consciousness (Gondolf and Williams 2001). Alternatively, men without a high degree of racial and cultural awareness appear to function well in diverse groups.…”
Section: Efforts To Incorporate Cultural Content In Groupsmentioning
confidence: 98%
“…Researchers interested in possible links between case outcomes and domestic violence recidivism have examined the relative effects of diversions, nolles, dismissals, acquittals, convictions, batterer intervention programs, fines, probation, and jail sentences (e.g., Chen, Bersani, Myers, & Denton, 1989;Davis, Smith, & Nickles, 1998;Davis, Taylor, & Maxwell, 2000;DeMaris & Jackson, 1987;Dutton, 1986;Edelson & Grusznski, 1989;Fagan, 1989Fagan, , 1996Fagan, Friedman, Wexler, & Lewis, 1984;Feder & Dugan, 2002;Ford & Regoli, 1993;Gondolf, 1999;Gondolf & Williams, 2001;Gross et al, 2000;Hamberger & Hastings, 1988;Harrell, 1991;Healey, Smith, & O'Sullivan, 1998;Hirschel, Hutchinson, & Dean, 1992;Keilitz, Hannaford, & Efkeman, 1997;Mears, Carlson, Holden, & Harris, 2001;Murphy, Musser, & Maton, 1998;Palmer, Brown, & Barrera, 1992;Shepard, 1992;Steinman, 1990;Syers & Edleson, 1992;Tolman & Weiscz, 1995;Wallace & Seymour, 1999;Wolfe & Jaffe, 1999;Wooldredge & Thistlethwaite, 2005). This relatively large body of research focused primarily on batterer intervention programs and convictions, with little attention paid to incarceration.…”
Section: Case Outcomes and Subsequent Intimate Violencementioning
confidence: 98%